Morphology and biological features of phages extracted from moss and soils of Antarctic region - V. V. Holovan; O.M. Andriichuk; I. H. Budzanivska (Ukrainian Antarctic Journal, 2019)
Isolation of bacteriophages from ecosystems which function in low temperatures represents a huge scientific interest, although it has certain difficulties in methodology. One of the tasks, that solves this question, is the definition of the geographic range of phages distribution, investigation of their properties and evolutionary characteristics in different climatic conditions. The aim of the survey was to identify the presence of bacteriophages in moss and soil samples, which were taken at the Argentine Islands archipelago, to find structural elements of the virion and evaluate a variety of bacteriophages morphotypes in terrestrial biotope of Antarctica. Мethods: аnalyzed samples moss and soil, selected during seasonal work in 2017 on the Akademik Vernadsky station. The sterile material (5 g) was collected and put into 50 ml 0.1 M Tris-HCl buffer. The filtrate was centrifuged for 2 hours, 90000g (ОPTIMA L-90K (Beckman Coulter)). The sediment from each tube was resuspended in 0.5 ml 0.1 M Tris-HCl buffer (pH 7.0). Bacterial cultures were grown on nutrient agar and liquid broth (1.5% and 0.7%). The phages were detected by direct inoculation. The titers were measured in plaque-forming units per ml (PFU/ ml) via Gratia agar technique. The concentrated phage preparations were analyzed by electron microscopy. Contrasting was performed with 1—2% Tungsten Phosphoric Acid, pH 7—7.4. Results: аlso there were made conclusion about the activity of isolated phages. Due to the results of the EM, phages were divided into four taxonomic groups, according to the structural features: the family Podoviridae, C1 morphotypes, order Caudovirales; the family Siphoviridae, B1-B2 morphotypes, order Caudovirales; the family Myoviridae, A1, А3 morphotypes, order Caudovirales. The research revealed, that a phages are sensitive to various bacterial cultures, which differ in morphological and biochemical characteristics. Conclusions: the detection of lithic activity of phages against bacteria (Pseudomonas fluorescens 8573, P. syringae pv. lachrymans 7591 Serratia marcescens sp., Cq13) suggests the probability of the presence of specific mechanisms that allow them to acquire the ability to adapt to new hosts.